2014
DOI: 10.1017/s0144686x14000257
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory retirement for older professional drivers: an exploration of experiences for older Singaporean taxi drivers

Abstract: Singapore has an age-based mandatory retirement policy for taxi drivers. In 2006, the upper age limit of mandatory retirement was raised from 70 to 73 years for healthy, older taxi drivers. Retirement from taxi driving in Singapore often results in simultaneous retirement from work and forced driving cessation due to limited private vehicle ownership. While both retirement from work and driving cessation have been found to have negative implications for health and wellbeing in Western countries, little is know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
1
9
1
Order By: Relevance
“…After the calibration of many models, the results showed that such variables as age, education level, history of the current or previous disease, smoking, and physical disabilities were not significant in the prediction of PDO traffic accidents among taxi drivers of Tehran. However, this finding is contrary to the results of a number of previous studies [15,31]. This result might be due to the fact that taxi drivers spend much of their time in traffic and at the wheel; accordingly, they are expert in this field.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…After the calibration of many models, the results showed that such variables as age, education level, history of the current or previous disease, smoking, and physical disabilities were not significant in the prediction of PDO traffic accidents among taxi drivers of Tehran. However, this finding is contrary to the results of a number of previous studies [15,31]. This result might be due to the fact that taxi drivers spend much of their time in traffic and at the wheel; accordingly, they are expert in this field.…”
Section: Discussioncontrasting
confidence: 92%
“…The results of multiple regression and Poisson regression demonstrated that, with increasing minutes of daily exercise and decreasing the mental health problems, the number of PDO decreases among taxi drivers. This finding is in line with those of previous studies indicating that driving performance is affected by health related changes [31]. In addition, physical activity was shown to be a protective factor for hypertension among taxi drivers in Brazil, when considering the deleterious effect of time as a taxi driver [12].…”
Section: Discussionsupporting
confidence: 91%
“…From 2009 to 2011 an exploratory mixed method research programme was undertaken with UQDRIVE researchers to understand the range of retirement experience of older Singaporean taxi drivers, aged 70 to 73 years, in order to develop a relevant intervention (Chan, 2012). Retirement was found to be dominated by issues related to the loss of the valued worker role and a negative perception of ageing, with little focus on expected driving cessation issues such as missing driving itself or struggling with transportation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with current drivers, retired drivers significantly spent less time away from home, had reduced use of transportation, lower health-related quality of life while spending more time in solitary leisure and instrumental activities of daily living (ADL). While mandatory retirement was expected, most participants appeared poorly prepared for it (Chan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A Ministry of Community Development, Youth and Sports (2005) survey in Singapore found that the main reason why seniors sought post-retirement employment was to have the means to meet current expenses (62%). In contrast, ‘lifestyle choices’ of the type popularly stressed in Singapore's active ageing literature (Chan, Gustafsson and Liddle 2014; K. W. Wong 2013) were much less highly regarded. For example, only 14.1 per cent of respondents stated that they wanted ‘to lead an active life’ and half again as needing ‘something to occupy my time’ (Ministry of Community Development, Youth and Sports 2005).…”
Section: Comparing Predicaments In Hong Kong and Singaporementioning
confidence: 99%